A prospective randomised double blind study of the comparison of two opioids- fentanyl and buprenorphine – as adjuvant to spinal bupivacaine in caesarean sections - Sonya, Kamal; C. V., Davies (International Journal of Clinical Trials, 2017)
Background: Opioids are first introduced as additives to spinal anaesthesia in 1979, with intrathecal morphine as forerunner. Neuraxial opioids when added to local anaesthetics prolong the duration of sensory block, improve quality of block and no unwanted sympathetic blockade leading to hypotension. This prospective randomized double blind study was undertaken to evaluate the duration of analgesia, sensory and motor blocking properties and side effects of two opioids – Fentanyl and Buprenorphine, when used as adjuvant to spinal Bupivacaine in caesarean section. Methods: Sixty patients between the age group 18-35 years belonging to ASA I and II posted for elective LSCS were randomly divided into two groups. Each group consisting of 30 patients , received either 1.8 ml 0.5% Bupivacaine with 25 mcg Fentanyl (group F) or 1.8 ml 0.5% Bupivacaine with 75 mcg buprenorphine (Group B). The onset, maximum level and duration of sensory and motor blockade and hemodynamic parameters were monitored. Results: Maximum height of sensory block was achieved faster in fentanyl group (i.e. 4.09±1.12 minutes compared to 4.56±1.21 minutes in buprenorphine group). Duration of analgesia was significantly prolonged in buprenorphine group. It was 317±54 minutes and 214±35 minutes respectively for buprenorphine and fentanyl groups. Conclusions: The study thus concluded that although fentanyl produce faster sensory block, duration of analgesia is longer with buprenorphine, and both the drugs do not cause significant side effects.